2016
DOI: 10.3390/antiox5030024
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Diabetes: Does Obesity-Induced Oxidative Stress Drive the Aging Process?

Abstract: Despite numerous correlative data, a causative role for oxidative stress in mammalian longevity has remained elusive. However, there is strong evidence that increased oxidative stress is associated with exacerbation of many diseases and pathologies that are also strongly related to advanced age. Obesity, or increased fat accumulation, is one of the most common chronic conditions worldwide and is associated with not only metabolic dysfunction but also increased levels of oxidative stress in vivo. Moreover, obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 129 publications
0
25
0
6
Order By: Relevance
“…Numerous research studies suggest that oxidative stress has an important role in the process of aging. Accumulation of oxidative damage to cell and tissue over the lifespan leads to aging . Several evidences show that antioxidant supplements including resveratrol, are useful in delaying the aging process .…”
Section: The Effect Of Resveratrol On Aging Biomarkersmentioning
confidence: 99%
“…Numerous research studies suggest that oxidative stress has an important role in the process of aging. Accumulation of oxidative damage to cell and tissue over the lifespan leads to aging . Several evidences show that antioxidant supplements including resveratrol, are useful in delaying the aging process .…”
Section: The Effect Of Resveratrol On Aging Biomarkersmentioning
confidence: 99%
“…They, in turn, further exacerbate cardiovascular disease (CVD) [13]. Recent studies on db/db mice treated with Rapamycin for 4 weeks have shown that Rapamycin could improve cardiac contractile functions [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, hypercaloric diets that contain large amounts of refined sugars and fat produce brain damage and systemic oxidative stress (Freeman, Haley‐Zitlin, Rosenberger, & Granholm, ). For instance, high‐fat diet (HFD) stimulates the accumulation of adipose tissue, leading to the development of obesity, which is associated with increased oxidative stress in both humans and animal models (Hunsche et al., ; Panchal et al., ; Salmon, ). Thus, the oxidative stress produces a cellular dysregulation, increased production of proinflammatory molecules, energy imbalance, and increases the risk factors for type 2 diabetes, hypertension, hyperlipidemia, and brain damage (Ye, Zhang, Townsend, & Tew, ).…”
Section: Introductionmentioning
confidence: 99%